Restoring employer image after a crisis - Steiner, Zachary J., author; Byrne, Zinta S., advisor; Gibbons, Alyssa, committee member; Gingerich, Karla, committee member; Plaisance, Patrick, committee member (Colorado State University. Libraries, 2012)
Organizational image is a key predictor of employee recruitment variables, such as attraction to a company, intentions to pursue employment, and pursuit behavior. A company's image can suffer when faced with negative events or crisis. I applied image restoration theory from the crisis communication literature to explore the process by which a company's image can be restored post-crisis for job seekers. I also applied insights from research on the psychology of apologies to understand the mechanism by which a company's image changes in the context of image restoration. I employed a repeated measures 2 x 3 factorial experimental design. Time 1 information was either negative or neutral about a company. Time 2 information was one of two forms of image restoration (reduce offensiveness and corrective action) or neutral information about the same company. The study also examined a chain of recruitment outcomes from image to attraction, to intentions to pursue a job opportunity. As predicted, results suggest that participants who initially viewed negative information had lower image ratings than those who viewed neutral information at time 1. Those who initially viewed negative information at time 1 showed improvements in image perceptions at time 2 in response to new information, as hypothesized. However, at time 2 there were no differences in participants who were exposed to the image restoration as compared to the neutral information, contrary to predictions. Attraction fully mediated the relationship between image and intentions to purse a job opportunity, as hypothesized. This study provided an initial test of image restoration theory in a recruitment context. Though there were no observed differences between the two types of image restoration and neutral information conditions, all three conditions showed improvements in image perceptions at time 2. Results of the study suggest that the mere absence of negative information may serve as an image recovery mechanism for job seekers; hence, actual efforts to construct the message to include image restoration content that will restore image after a crisis event may not be necessary.
Keywords: crisis communication; recruitment; organizational image; employer image